TGF-β2 enhances expression of equine bone marrow-derived mesenchymal stem cell paracrine factors with known associations to tendon healing - Drew W. Koch; Lauren V. Schnabel; Ilene M. Ellis; Rowan E. Bates; Alix K. Berglund (Stem Cell Research & Therapy, 2022)
Abstract Background Mesenchymal stem cells (MSCs) secrete paracrine factors and extracellular matrix proteins that contribute to their ability to support tissue healing and regeneration. Both the transcriptome and the secretome of MSCs can be altered by treating the cells with cytokines, but neither have been thoroughly investigated following treatment with the specific cytokine transforming growth factor (TGF)-β2. Methods RNA-sequencing and western blotting were used to compare gene and protein expression between untreated and TGF-β2-treated equine bone marrow-derived MSCs (BM-MSCs). A co-culture system was utilized to compare equine tenocyte migration during co-culture with untreated and TGF-β2-treated BM-MSCs. Results TGF-β2 treatment significantly upregulated gene expression of collagens, extracellular matrix molecules, and growth factors. Protein expression of collagen type I and tenascin-C was also confirmed to be upregulated in TGF-β2-treated BM-MSCs compared to untreated BM-MSCs. Both untreated and TGF-β2-treated BM-MSCs increased tenocyte migration in vitro. Conclusions Treating equine BM-MSCs with TGF-β2 significantly increases production of paracrine factors and extracellular matrix molecules important for tendon healing and promotes the migration of tenocytes in vitro.